Efek penutupan Diastema menggunakan Silicone Guide dengan Komposit Nanofiller: Laporan Kasus - Rudy Djuanda; Fadli Azhari (Intisari Sains Medis, 2018)
Background: Midline diastema is an aesthetic problem that can occur in anterior teeth where the closure of it can be performed by direct composite restorations. This study aims to see the benefits of using silicone guides and nanofiller composite resins to provide a smooth and esthetic restoration surface effect on the diastema closure.Case Description: A 24-year-old woman came to the clinic with complaints of a gap in the front teeth which was considered to be very disturbing appearance. Patients had a desired to fix their teeth due to uncomfortable feeling when smiling. Clinically, there was a diastema between the teeth 11 and 21. There was no caries found and teeth were found to be vital. While other teeth had a normal shape and there was no gap between the teeth. The gingival tissues around the tooth look normal and good oral hygiene and there was no low frenulum. Diastema closure using nanofiller composite restorations showed a good prognosis.Conclusion: Midline diastema closure using silicone guide can provide precise results according to the analysis, either on the anatomy of the palatal, labial and dental midline. The use of nanofiller composite resins at the closure of midline diastemic can provide advantages of both strength and maximum polishing results.